Isolation of Alkaloids from Papaver rhoeas (Papaveraceae) Wildly Grown in Iraq - Ayad Lafta, Amenah; N. Hamad, Maha (Iraqi Journal of Pharmaceutical Sciences, 2021)
The plant Papaver rhoeas ,which belongs to family Papaveraceae and known as common poppy is wildly grown in Iraq .It was used in traditional medicine in wide range of diseases including inflammation, diarrhea, sleep disorders, treatment of cough, analgesia, and also to reduce the withdrawal signs of opioid addiction.The project provide the first comprehensive research done in Iraq to study the phytochemical and the methods of extraction and separation of alkaloids from Papaver rhoeas wildly grown in Iraq .The plant was harvested in April 2019 from Zurbatiya is an Iraqi town located at the northeast of Waist province in Iraq.The collected plant was washed thoroughly, dries under shade, and grounding in a mechanical grinder to fine powder. The plant was extracted by hot extraction method using Methanol then fractionation was done to separate alkaloids from chloroform Fraction by TLC and PTLC .The alkaloids were isolated and purified by PTLC then subjected to various analytical techniques for alkaloids identification such as UV, LC mass and IR .The result was indicated of three alkaloids (dihydrocodien, chelidonine and papaverrubine C) in Papaver rhoeas plant.